2015
DOI: 10.1177/1071100715598602
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Dorsal Wedge Osteotomy for Pediatric Freiberg Disease

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The osteotomy site was fixed with two small K-wires (cross-pinning).Some osteotomies which were rotationally stable were fixed with single thick K-wire. Young patients had greater improvement in score in Kitaoka et al 11 scoring system in our study as was seen by Bruno S Pereira et al 13 Gauther and Elbaz 7 in their study on 53 patients treated by dorsiflexion osteotomy found only one patient with persistent pain. Chao and co-workers 12 reported two poor results from thirteen patients with all stages of Freiberg's disease who were treated with dorsal closing wedge osteotomy.…”
Section: Discussionsupporting
confidence: 81%
“…The osteotomy site was fixed with two small K-wires (cross-pinning).Some osteotomies which were rotationally stable were fixed with single thick K-wire. Young patients had greater improvement in score in Kitaoka et al 11 scoring system in our study as was seen by Bruno S Pereira et al 13 Gauther and Elbaz 7 in their study on 53 patients treated by dorsiflexion osteotomy found only one patient with persistent pain. Chao and co-workers 12 reported two poor results from thirteen patients with all stages of Freiberg's disease who were treated with dorsal closing wedge osteotomy.…”
Section: Discussionsupporting
confidence: 81%
“…While long-term follow-up studies have recently begun to demonstrate the efficacy of dorsal wedge closing osteotomies for the treatment of Freiberg’s disease, the best approach for failed operative management of the disease remains in question. 14 Five out of 13 patients in our cohort failed not only conservative management but also previous operative management for Freiberg’s. Therefore, it is important to note that a common use of PVA implant in our study cohort was in the setting of a previously failed operative treatment.…”
Section: Discussionmentioning
confidence: 86%
“…8 Despite good long-term results for operative treatment of most stages of Freiberg's disease, late-stage disease and failed primary procedures present a challenge. 5,7,8,12,14 Salvage options for failed osteotomies and advanced second MT head arthritis include resection arthroplasty, joint debridement, osteotomy, and osteochondral transplant. 4 More recently, synthetic cartilage implants have been demonstrated in clinical trial to be safe and efficacious in treating advanced stage hallux rigidus, offering pain relief while preserving motion at the MTP joint.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 study could be found that reported the long-term results of osteotomy. Pereira et al 27 reported that after a mean follow-up period of 23.4 years of 20 patients in the pediatric age group, the mean AOFAS score was 96.8, and all the patients had good to excellent results. However, 85% of the patients in that study were grades 2 and 3, there were no cases of grade 5, and there was a negative correlation between the AOFAS score at the final follow-up and disease grade.…”
Section: Discussionmentioning
confidence: 99%